CURRENT TREND IN RESEARCH ABOUT INVISALIGN® SUCCESS OUTCOME: A SYSTEMATIC REVIEW USING PRISMA GUIDELINE - Zakyah, Akhyar Dyni; Laviana, Avi (Odonto : Dental Journal, 2021)
ABSTRACTBackground: While some researches have claimed that Invisalign® is successful in creating meaningful tooth movement, there is still no comprehensive literature review that summarizes them using one valid and reliable parameter. American Board of Orthodontics-Model Grading System (ABO-MGS) is an objective measurement for the success of orthodontic treatment. This systematic review is determined to provide scientific pieces of evidence to prove the truth of the claim using ABO-MGS. Method: English-based health sciences journal databases were searched using "Invisalign" and "Model Grading System". The databases included in this study were Pubmed, Ebscohost, Google Scholar, ScienceDirect, and MEDLINE. Inclusion criteria were clinical cross-sectional, cohort, or case-control study using human subjects who finished Invisalign treatment. Two independent authors summarized the data from the obtained articles using predefined data fields and discussed the data result together. Result: Out of 60 studies found during the identification process, only 6 studies were included in the qualitative analysis. Only one of them studied the efficacy of Invisalign® by using ABO-MGS to measure the pre- and post-treatment model. Invisalign® mostly successful in creating change for alignment, overjet, and interproximal contact. Other categories were not that successful to be treated with Invisalign. Conclusion: Invisalign®‘s success is mostly pursued by correcting the malocclusion in the anterior region. Given the scarce amount of reliable evidence available, it is suggested that more studies are required to be able to draw a further conclusion.